Potential immunological effects of gender-affirming hormone therapy in transgender people – an unexplored area of research. (December 2022) - White, Alice A.; Lin, Ashleigh; Bickendorf, Xander; Cavve, Blake S.; Moore, Julia K.; Siafarikas, Aris; Strickland, Deborah H.; Leffler, Jonatan
There are well-described sex-based differences in how the immune system operates. In particular, cisgender (cis) females have a more easily activated immune system; associated with an increased prevalence of autoimmune diseases and adverse events following vaccinations. Conversely, cis males have a higher threshold for immune activation, and are more prone to certain infectious diseases, such as coronavirus disease (COVID-19). Oestrogen and testosterone have immune-modulatory properties, and it is likely that these contribute to the sexual dimorphism of the immune system. There are also important immune-related genes located on the X chromosome, such as toll-like receptor (TLR) 7/8; and the mosaic bi-allelic expression of such genes may contribute to the state of immune hyperactivation in cis females. The scientific literature strongly suggests that sex-based differences in the functioning of the immune system are related to both X-linked genes and immune modulation by sex hormones. However, it is currently not clear how this impacts transgender (trans) people receiving gender-affirming hormonal therapy. Moreover, it is estimated that in Australia, at least 2.3% of adolescents identify as trans and/or gender diverse, and referrals to specialist gender-affirming care are increasing each year. Despite the improving social awareness of trans people, they remain chronically underrepresented in the scientific literature. In addition, a small number of case studies describe new onset autoimmune disorders in adult trans females following oestrogen use. However, there is currently minimal long-term research with an immunological focus on trans people. Therefore, to ensure the positive health outcomes of trans people, it is crucial that the role of sex hormones in immune modulation is investigated further.